2008
DOI: 10.1086/591621
|View full text |Cite
|
Sign up to set email alerts
|

A Cosmologically Motivated Description of the Dark Matter Halo Profile for the Low Surface Brightness Galaxy, Malin 1

Abstract: In this paper we derive a possible mass profile for the low surface brightness galaxy, Malin 1, based upon previously published space-based and ground-based photometric properties and kinematics. We use properties of the bulge, normal disk, outer extended disk and H I mass as inputs into mass profile models. We find that the dark matter halo model of Malin 1 is best described by a halo profile that has undergone adiabatic contraction, inconsistent with the findings for most disk galaxies to date, yet consisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
(119 reference statements)
1
10
0
Order By: Relevance
“…Indeed, these data seem consistent with the suggestion that pitch angle and mass concentration are related [27,28]. [26], the red squares are galaxies from Seigar et al [27], the blue squares are galaxies from Seigar et al [28], the cyan square is for Malin 1 [64], the green square is for M31 [34], and the magenta square represents the data for M33 (this paper). Finally Figure 5 shows a plot of supermassive black hole mass as a function of NFW concentration parameter.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, these data seem consistent with the suggestion that pitch angle and mass concentration are related [27,28]. [26], the red squares are galaxies from Seigar et al [27], the blue squares are galaxies from Seigar et al [28], the cyan square is for Malin 1 [64], the green square is for M31 [34], and the magenta square represents the data for M33 (this paper). Finally Figure 5 shows a plot of supermassive black hole mass as a function of NFW concentration parameter.…”
Section: Discussionsupporting
confidence: 86%
“…For M31, the pitch angle is the average of values taken from Arp [66] and Braun [67]. The NFW concentration value is taken from (1) Seigar [64], (2) Klypin et al [68], (3) Seigar et al [34], and (4) Seigar et al [28]. The black hole mass estimates are taken from (5) Ghez et al [69], (6) Bender et al [54], and (7) Gebhardt et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…12 M e , which makes Malin 1an enormous dark matter reservoir (Seigar 2008). The galaxy has been also an interesting target for Spitzer (Rahman et al 2007) and for sub-millimeterobservations (Das et al 2006), for searching both warm and cold dust, as well as fordetecting emission from molecular clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent analysis of a Hubble Space Telescope ( HST ) I ‐band image suggests that Malin 1 has a normal barred inner spiral disc embedded in a huge diffuse LSB envelope (Barth 2007). Based on previously published photometric characteristics and H i kinematics, Seigar (2008) derived a possible mass profile for Malin 1. He concluded that the galaxy is baryon dominated in the centre (out to ∼10 kpc) and, probably, has parameters typical of normal galaxies (of course, excluding the giant LSB envelope).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lelli et al (2010; see also Sancisi & Fraternali 2007) presented similar results using their re‐analysis existing H i data. The models by Seigar (2008) and Lelli et al (2010) are based on published H i observation by Pickering et al (1997). But these H i data are strongly affected by beam smearing and, as a result, no reliable kinematics inside the central 15 kpc are currently available.…”
Section: Introductionmentioning
confidence: 99%